The Brief Review on the Green Technology and its Numerous Uses (International Journal of Innovative Research in Engineering & Management, 2021)
Technology" refers to the use of science for practical reasons.  The field of "green technology" encompasses a rapidly growing  ommunity of techniques and materials, ranging from energy generation tactics to non-toxic cleaning solutions. This article  also focuses on the same subject of green technology and its  many applications, but in greater depth or in a more  diagrammatic manner, such as an overview of green technology,  which includesthe definition of green technology and the  numerous kinds of green technology (Ocean Energy, Solar  Energy and Wind Energy etc.). This paper also discusses the  various advantages and disadvantages of green technology (such  as sewage treatment, capture and storage technology, renewable  energies, solid waste treatment and management, and water  treatment), as well as the various applications of green  technology (such as sewage treatment, capture and storage  technology, renewable energies, solid waste treatment and management, and water treatment). Using environmentally  friendly technologies Companies and utility providers are taking  the necessary measures and exerting considerable effort to meet  societal needs with long-term solutions that may be utilized now  and in the future without creating environmental harm or  depletion.
Keywords: Carbon; Energy; Green Technology; Solar Energy; Sustainable